2018
DOI: 10.1186/s12864-018-4678-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of microRNAs associated with the exogenous spermidine-mediated improvement of high-temperature tolerance in cucumber seedlings (Cucumis sativus L.)

Abstract: BackgroundHigh-temperature stress inhibited the growth of cucumber seedlings. Foliar spraying of 1.0 mmol·L− 1 exogenous spermidine (Spd) to the sensitive cucumber cultivar ‘Jinchun No. 2’ grown at high-temperature (42 °C/32 °C) in an artificial climate box improved the high-temperature tolerance. Although there have been many reports on the response of microRNAs (miRNAs) to high-temperature stress, the mechanism by which exogenous Spd may mitigate the damage of high-temperature stress through miRNA-mediated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 68 publications
1
24
0
Order By: Relevance
“…Genes respond to high‐temperature stress via changes in expression levels. Wang et al () identified the first set of miRNAs associated with the exogenous Spd‐mediated improvement of high‐temperature tolerance in cucumber seedlings. For example, 34 specific lncRNAs were identified under heat stress and 192 target genes were regulated by lncRNAs, most of which were thermo‐responsive genes (Song et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Genes respond to high‐temperature stress via changes in expression levels. Wang et al () identified the first set of miRNAs associated with the exogenous Spd‐mediated improvement of high‐temperature tolerance in cucumber seedlings. For example, 34 specific lncRNAs were identified under heat stress and 192 target genes were regulated by lncRNAs, most of which were thermo‐responsive genes (Song et al ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the effects of exogenous Spd and MGBG on the growth and physiological indicators of resistance in cucumber seedlings under salt stress were analyzed, and the results were in accord with the results of previous studies. Wang et al [32] described the molecular mechanism of exogenous Spd on improving high-temperature tolerance based on the expression of miRNA in cucumber. Sang et al [33] used proteomics studies to analyze the effects of Spd on alleviating high-temperature stress in tomato.…”
Section: Discussionmentioning
confidence: 99%
“…After treatment for 7 d, the growth parameters were measured by the method of Wang et al [32] and Tang et al [52].…”
Section: Salt Stress and Spd Treatmentmentioning
confidence: 99%
“…Multiple studies of the stress response of vegetables under various abiotic stress conditions have been performed (Gous et al, 2016;Wang et al, 2018;Zhou et al, 2013). Studies of HS on vegetables have mainly focused on HSPs and relative enzymes.…”
mentioning
confidence: 99%
“…Under high-temperature stress, ABA could induce the expression of HSP70, leading to its tolerance to heat in cucumber (Li et al, 2015). MicroRNAs were related to improvements in the high-temperature tolerance of cucumber seedlings (Wang et al, 2018). Ten quantitative trait loci (QTLs) (rate of contribution, 6% to 17%) influencing HS in cucumber have been detected (Chen et al, 2008).…”
mentioning
confidence: 99%